2010
DOI: 10.1096/fj.10-154757
|View full text |Cite
|
Sign up to set email alerts
|

The melanoma-associated transmembrane glycoprotein Gpnmb controls trafficking of cellular debris for degradation and is essential for tissue repair

Abstract: Kidney damage due to injury rarely resolves completely, and there are currently no therapies capable of promoting repair. In addition to understanding mechanisms by which tissues are damaged, illuminating mechanisms of repair and regeneration is also of great importance. Here we show that the melanoma-associated, transmembrane glycoprotein, Gpnmb, is up-regulated 15-fold following ischemic damage in kidney tissue and by more than 10-fold in macrophages and 3-fold in surviving epithelial cells. Gpnmb-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 49 publications
5
88
0
Order By: Relevance
“…Previous studies have shown that GPNMB enhances tissue repair by inducing autophagy and also promotes angiogenesis during tumor growth (36,37,40). We have recently identified GPNMB as one of the targets for miR-150 (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that GPNMB enhances tissue repair by inducing autophagy and also promotes angiogenesis during tumor growth (36,37,40). We have recently identified GPNMB as one of the targets for miR-150 (34).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms for the resistance in KO neonates are unknown. A recent study has implicated GPNMB in tissue protection by promoting autophagy (40), which induces the autophagy process by directly binding to a microtubule-associated protein 1A/1B-light chain 3/autophagyrelated protein 8, thereby enhancing the fusion of an autophagosome with a lysosome. The induction of autophagy further helps in clearing cellular debris, thus reducing inflammation and cellular injury.…”
Section: Discussionmentioning
confidence: 99%
“…32 Grids were scanned using a Philips 410 electron microscope for mouse studies (Philips Export BV, Eindhoven, The Netherlands) and a JEOL 1011 electron microscope (Japan) for human studies.…”
Section: Electron Microscopymentioning
confidence: 99%
“…A part of the reparative process involves phagocytosis and clearance of dead cells, debris, and oxidized matrix. Reparative macrophages express high levels of scavenger receptors and lysosomal pathway proteins, including the transmembrane glycoprotein gpNMB (60,62), which serve this clearance purpose. In addition, such reparative macrophages produce growth factors, which stimulate tubular cell and microvascular regeneration.…”
Section: Contribution Of Other Cells To Fibrogenesismentioning
confidence: 99%